Language Style of Beauty and Kencana Wungu's Position in Damarwulan Manuscript (Ethnolinguistic) - Utami, Respati Retno; Lestari, Tri Edliani (Sutasoma : Jurnal Sastra Jawa, 2021)
The purpose of this study was to analyze the style of language about the portrayal of female characters in Damarwulan Manuscript, namely Kencana Wungu queen. The position of women in Serat (Manuscript) Damarwulan is a very interesting part. Kencanawungu figure is a woman who is able to have power, different from the role of women found in other classical texts that only make women as Queen/king. The style of language used to describe the figure of Kencana Wungu who has the highest beauty and position is to use a panyandra (language style). Women actually have power like two blades. Women are able to destroy the world of men, but on the contrary women can also reassure the world. The study used to analyze the style of language about beauty and also the position of Kencana Wungu in Damarwulan Manuscript is an ethnolinguistic study. The method used in this study are two, namely the foundation method and ethnographic method. The foundation method is used because the object of this research is in the form of an old text, namely Damarwulan Manuscript. Ethnographic methods are used to analyze the style of language and the position of women based on Javanese cultural perspectives. This study seeks to show the style of language in expressing feelings of love and trying to describe the position of women in Damarwulan Manuscript. In addition, this research can contribute to ethnographic research, especially in the field of ancient manuscripts. Through this study, we can find out the richness of the repertoire of language styles owned by the Javanese. Javanese poets use panyandra which is related to the beauty of nature and fauna to describe the beauty of a woman. Keywords: language style, beauty, female position, Damarwulan Manuscript